New ecological and taxonomic remarks on Sabinella troglodytes and Nanobalcis worsfoldi (Gastropoda: Eulimidae) living on the “slate-pencil sea urchin” from the Mexican Caribbean region - González Vallejo, Norma Emilia; De León González, Jesús Ángel (Universidad Autonóma de México. Instituto de Biología, 2018)
Abstract Eulimidae is one of the most diversified families among marine parasitic gastropods. They are usually reported associated with echinoderms, but for most described species the host is unknown, and few biological aspects of the symbiosis are known. As part of a larger study on eulimids, 300 sea urchins were collected in shallow water reef lagoons. Some were kept alive in the laboratory for 1 week and photographed and filmed under stereomicroscopes. Nanobalcis worsfoldi lives around and at the base of primary spines of the sea urchin Eucidaris tribuloides and is very abundant, whereas Sabinella troglodytes lives attached inside a gall that it builds from primary spines, and is uncommon. A complete characterization of the shells and morphology data for both eulimids are included. The comparison of our specimens with type and non-type material indicates several noteworthy features. We found higher and wider whorls, variation in position of growth scars and total number of whorls. We suggest that there is a species complex for Sabinella troglodytes. Mantle pigmentation patterns, mode of attachment, live displacement, and other ecological observations on the host are presented for the first time for both species from the Mexican Caribbean Sea. Keywords: Ectoparasites; Echinoderms; Eucidaris; Shallow water; Symbiosis Resumen Eulimidae es una de las familias más diversificadas entre los gasterópodos marinos parásitos. Por lo general, se reportan asociados con equinodermos, pero para la mayoría de las especies descritas, el huésped es desconocido y pocos aspectos biológicos de la simbiosis son conocidos. Como parte de un estudio más amplio sobre eulímidos, se recogieron 300 erizos de mar en lagunas arrecifales de aguas poco profundas, algunos se mantuvieron vivos en el laboratorio durante una semana y fueron fotografiados y filmados bajo el microscopio estereoscópico. Nanobalcis worsfoldi vive alrededor y en la base de las espinas primarias del erizo de mar Eucidaris tribuloides y es muy abundante, mientras que Sabinella troglodytes, vive adherido dentro de una agalla que construye en las espinas primarias y es poco común. Se incluye una caracterización completa de los datos de conchas y morfología para ambos eulímidos. La comparación de nuestros especímenes con material tipo y no-tipo, reveló varias características notables. Encontramos la vuelta principal del cuerpo más alta y más anchas, variación en la posición de las cicatrices de crecimiento y el número total de vueltas. Sugerimos que existe un complejo de especies para Sabinella troglodytes. Los patrones de pigmentación del manto, el modo de adherirse, desplazamiento en vivo y otras observaciones ecológicas en el huésped se presentan por primera vez para ambas especies del mar Caribe mexicano. Palabras clave: Ectoparásitos; Equinodermos; Eucidaris; Agua poco profunda; Simbiosis